Isolation of Litylenchus coprosma from Coprosma macrocarpa, a new host and distribution in New Zealand - Xu, Yu Mei; Zhao, Zeng Qi; Alexander, Brett J. R.; Li, Dongmei (Zootaxa, 2019)
Coprosma macrocarpa, known as the large-seeded coprosma or coastal karamu, is a shrub endemic to New Zealand. To our knowledge, no reports of plant parasitic nematodes associated with C. macrocarpa have been reported. Here we report the detection and identification of the nematode, Litylenchus coprosma, extracted from C. macrocarpa in Otata Island.